2016
DOI: 10.11131/2016/101198
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane X Receptor and Cancer: Context-Specificity is Key

Abstract: Pregnane X receptor (PXR) is an adopted orphan nuclear receptor that is activated by a wide-range of endobiotics and xenobiotics, including chemotherapy drugs. PXR plays a major role in the metabolism and clearance of xenobiotics and endobiotics in liver and intestine via induction of drug-metabolizing enzymes and drug-transporting proteins. However, PXR is expressed in several cancer tissues and the accumulating evidence strongly points to the differential role of PXR in cancer growth and progression as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 141 publications
0
47
0
2
Order By: Relevance
“…It is possible to alleviate chemoresistance in some cases if a clinical anticancer drug can antagonize the drug-activated hPXR at therapeutic concentrations during combination chemotherapy. Our results are specifically relevant to cancers where hPXR activation contributes to chemoresistance via the upregulation of hPXR target genes (https://www.oncomine.org) (Pondugula and Mani, 2013;Pondugula et al, 2016).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It is possible to alleviate chemoresistance in some cases if a clinical anticancer drug can antagonize the drug-activated hPXR at therapeutic concentrations during combination chemotherapy. Our results are specifically relevant to cancers where hPXR activation contributes to chemoresistance via the upregulation of hPXR target genes (https://www.oncomine.org) (Pondugula and Mani, 2013;Pondugula et al, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have shown that elevated levels of PXR-mediated expression of drug-metabolizing enzymes and drug-efflux pumps in cancer cells contribute to increased resistance toward chemotherapy drugs (Pondugula and Mani, 2013;Planque et al, 2016;Pondugula et al, 2016). For instance, the activation of hPXR-mediated expression of drug-metabolizing enzymes and drug-efflux pumps decreases the sensitivity of human colon cancer cells, including LS174T cells, to several chemotherapy drugs such as SN-38 [the active metabolite of irinotecan (C 22 H 20 N 2 O 5 )] (Pondugula et al, 2016). Because BEL inhibited the hPXR agonist-activated expression of CYP3A4 and MDR1 in LS174 cells, we determined whether BEL inhibits RIF-induced resistance to SN-38.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP3A4 is probably the most important CYP enzyme for metabolism of chemicals, and for this reason, the induction and variability of CYP3A4 are important modifying factors in a large number of chemical‐induced toxicities, especially regarding pharmaceuticals . For example, anticancer therapy‐related adverse effects have been associated with CYP3A4 variability due to induction and genetic polymorphisms in breast, prostate, gynaecological and colorectal cancers , and consequently, the interest of using nuclear receptor activation and target gene induction as biomarkers for revealing potential risks and for the translation into successful treatments of diseases has grown during the recent years .…”
Section: The Central Role Of Xenobiotic Receptors and Cyp Induction Imentioning
confidence: 99%
“…The activation of AhR by bacterial-derived tryptophan metabolites elicits anti-inflammatory and tumor-suppressive effects in the colon [6366]. PXR also regulates cell proliferation, metastasis, and inflammation [67]; as such, bacterial metabolites of tryptophan that activate this receptor may affect the development and severity of colonic inflammation and colon cancer.…”
Section: Tryptophan Metabolitesmentioning
confidence: 99%